The Image of the Child in Jordanian Cinema: A Semiotic Study of "Theeb" (Journal of Namibian Studies : History Politics Culture, 2023)
This research shows the image of the child in the Jordanian cinema. The study sample consisted is the semiotic analysis of the cinematic film "Theeb", where the researcher worked on analyzing four scenes (Master scene) from the film: the longest daytime scene, the longest night scene, the shortest daytime scene, and the shortest night scene, and analyze them semiologically. The researchers used Roland Barthes's theory of semiotic analysis. Roland Barthes divides the visual message into two parts, the "iconic message" which includes two connotations (designative and applied connotation) and the "linguistic message" (structural function and approach).The results indicated that the term child image in Jordanian and Arab cinema is a newly established term. Many individual initiatives have emerged that presented the image of the child in films and series. In general, the image of the child in the cinema has disappeared with the project to promote the child's dreams and what he aspires to in the future.